Perioperative anesthetic challenges in pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension: A case series - Khushboo Mehta,; Ira Balakrishnan M,; Richa Chauhan,; Virendra Kumar, (Asian Journal of Medical Sciences, 2025)
Pulmonary arterial hypertension as a result of the occlusion of the branches of the pulmonary vasculature is characterized by a rise in the mean pulmonary arterial pressure above 20 mmHg. Pulmonary endarterectomy is the preferred treatment modality for chronic thromboembolic pulmonary hypertension. Anesthetic challenges include management of right ventricular (RV) dysfunction, low baseline oxygen saturation, pre-operative deranged coagulation profile due to anticoagulant use, specific requirements for deep hypothermic circulatory arrest, and need for cerebral protection. Postoperatively, massive pulmonary hemorrhage, reperfusion pulmonary edema, residual pulmonary hypertension, and RV dysfunction may lead to prolonged intensive care unit stay and mechanical ventilation. We present a case series of the first seven endarterectomies in our institution, intending to highlight the perioperative anesthetic management of such patients.